PELATIHAN MEMBUAT PERENCANAAN USAHA YANG BAIK SEBAGAI UPAYA PENINGKATAN KEMAMPUAN PENGELOLAAN USAHA - Hardjanti, Adiati; Purnami Kusumasari, R.A. Hera; -, Charlie (DEVOSI, 2021)
Community Service Activities were carried out in Tegal Alur Village, Kalideres District, West Jakarta. The problem faced by partners is the lack of training that can open up profitable business opportunities for them. The implementation method is carried out starting with a site survey, followed by training and ending with activity analysis. The Lean Canvas planning method is used to get to the heart of the idea, putting all the information on one page, helping to define the main information needed, without unnecessary details. As a result of this training activity, housewives, Family Welfare Development mother (PKK), youth organizations and Micro, Small and Medium Enterprises (UMKM) in Tegal Alur Village, West Jakarta, can start a business by taking action step by step, so that their efforts can generate profits as expected. It can be concluded that this training is beneficial for the community and increases the desire to become entrepreneurs.